Upaya Peningkatan Pengetahuan Hipertensi Melalui Sosialisasi Kepada Masyarakat di Desa Pemanggilan, Natar, Lampung Selatan - Isnaini, Nanda (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2024)
Hypertension is a condition that is often asymptomatic and characterized by a sustained increase in blood pressure, where systolic blood pressure exceeds 140 mmHg and diastolic blood pressure exceeds 90 mmHg. This can lead to more serious complications such as heart failure, kidney failure and stroke. The method used was socialization related to hypertension disease, prevention efforts and medicinal plants that can control blood pressure when consumed. The plants used are celery and rosella which are made specifically in the form of tea to help maintain blood pressure stability.Data on the level of community knowledge was taken, then analyzed and presented in the form of graphs. The results obtained with this socialization to the community, it is known that the level of knowledge and understanding of the community has increased significantly.